1999
DOI: 10.1512/iumj.1999.48.1664
|View full text |Cite
|
Sign up to set email alerts
|

Two-ended hypersurfaces with zero scalar curvature

Abstract: In many ways hypersurfaces with null r-th curvature function H r behave much like the minimal ones (H 1 = 0). One such manifestation is the following result to be proved in this paper, which extends to scalar-flat hypersurfaces (H 2 = 0) a well-known theorem of R. Schoen.Theorem. The only complete scalar-flat embeddings M n ⊂ R n+1 , free of flat points, which are regular at infinity and have two ends, are the hypersurfaces of revolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 0 publications
2
32
0
Order By: Relevance
“…It was proved by Hounie and Leite in a general point of view, see [9]. In fact, P 1 positive definite implies L 1 (f ) = div(P 1 (∇f )) is an elliptic differential operator.…”
Section: Preliminary Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It was proved by Hounie and Leite in a general point of view, see [9]. In fact, P 1 positive definite implies L 1 (f ) = div(P 1 (∇f )) is an elliptic differential operator.…”
Section: Preliminary Resultsmentioning
confidence: 94%
“…In [9], Hounie and Leite showed that L 1 is elliptic if and only if rank A > 1. Thus, K = 0 everywhere implies L 1 is elliptic, and if H > 0, then P 1 is a positive definite linear operator.…”
Section: Introductionmentioning
confidence: 99%
“…Observe that there are many examples of zero scalar curvature hyper-surfaces with finite total curvature which are not flat. See the examples provided by Lounie and Leite [13]. Clearly the analogy of our previous theorem with only the scalar flat assumption cannot be true.…”
Section: Theorem 11 Let M N (N > 2) Be a Complete And Noncompact Hypmentioning
confidence: 92%
“…Hence, it will be equally interesting to consider other elementary symmetric functions of the second fundamental form. In particular, it is natural to ask whether hyper-surfaces with zero scalar curvature have Bernstein type property [2,6,10,17]. However, observe that the equation for the hyper-surfaces with zero mean curvature is elliptic, the analogy for surfaces with zero scalar curvature is only a degenerate elliptic equation.…”
mentioning
confidence: 99%
“…. , k n of an orientable hypersurface x : M n → R n+1 given by A breakthrough in the study of these hypersurfaces occurred in the last five years of last century: in (Hounie and Leite 1995) and (Hounie and Leite 1999) conditions for the linearization of the partial differential equation S r+1 = 0 to be an elliptic equation were found. This linearization involves a second order differential operator L r (see the definition of L r in Section 2) and the Hounie-Leite conditions read as follows:…”
Section: Introductionmentioning
confidence: 99%